2020
DOI: 10.1021/acs.jced.0c00625
|View full text |Cite
|
Sign up to set email alerts
|

Charge Regulation of Natural Amino Acids in Aqueous Solutions

Abstract: The aim of this work is to develop a predictive model to describe the electrostatic behavior of 20 natural amino acids under diverse solution conditions. A coarse-grained model is proposed to account for the key ingredients of thermodynamic nonideality arising from the interaction of amino acids with various solvated ions in an aqueous solution including the molecular volume excluded effects, solvent-mediated electrostatic interactions, van der Waals attraction, and hydrophobic and hydration forces. With a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Toward that end, we employ an augmented primitive model (APM) that explicitly accounts for the different charged states of natural amino acids. 21 Due to the variation of hydration structure in response to the deprotonation or protonation of ionizable sites, each amino-acid molecule has a unique hard-sphere diameter σ i and valence Z i in different charged states.…”
Section: A Coarse-grained Model For Amino-acid Adsorptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Toward that end, we employ an augmented primitive model (APM) that explicitly accounts for the different charged states of natural amino acids. 21 Due to the variation of hydration structure in response to the deprotonation or protonation of ionizable sites, each amino-acid molecule has a unique hard-sphere diameter σ i and valence Z i in different charged states.…”
Section: A Coarse-grained Model For Amino-acid Adsorptionmentioning
confidence: 99%
“…We demonstrated in our previous work that the augmented model is able to reproduce both the titration behavior and the thermodynamic properties of amino-acid solutions in good agreement with experimental observations. 21 The coarse-grained model can be similarly applied to the adsorption of amino acids at an inorganic surface. In this case, the surface is represented by a hard wall with the charge density determined from the dissociation equilibrium of ionizable sites and ionic distributions self-consistently.…”
Section: A Coarse-grained Model For Amino-acid Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…These oligopeptides are composed of some or all of the following amino-acid residues: alanine, lysine and aspartic acid. The equilibrium constants for two ionizable residues are taken from our previous work: p K Lys = 10.95 and p K Asp = 3.97. The experimental data used for the validation of our theoretical results are from Imamura et al Unfortunately, no titration data were reported for the titanium dioxide surface used in the experimental work for oligopeptide adsorption.…”
Section: Resultsmentioning
confidence: 99%